A Critical Introduction to Language Evolution Current Controversies and Future Prospects - Progovac, Ljiljana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a critical introduction to the current views and controversies regarding language evolution. It sheds new light on hot topics such as: How ancient is language? Did Neanderthals have some form of language? Did language evolve gradually and incrementally, through stages, or suddenly, in one leap, in all its complexity? Does language evolution involve natural selection or not? This book is essential reading for scholars and students interested in language evolution, especially those in the fields of linguistics, psychology, biology, anthropology, and neuroscience. .
Editor introduction; Helen Aristar-Dry -- 1. Introduction to Divergent Views -- 2. Sudden (Saltationist) Approaches to Language Evolution -- 3. Gradualist Approaches to Language Evolution -- 4. Putting it all Together: The Language-Brain-Genes Loop.
Keywords: Language and languages; Grammar, Comparative and general -- Syntax; Linguistics; Anthropological linguistics; Psycholinguistics; Language History; Syntax; Linguistics; Linguistic Anthropology; Psycholinguistics and Cognitive Lingusitics